Implementation of the Law of the Republic of Indonesia No. 8 of 2019 in the Practice of Hajj Organization by Travel Agencies Using Non-Hajj Visas (A Case Study at PT Mirbath Tour and Travel Palu) - M. Dawud Arif Khan; Rugaiyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon of using non-Hajj visas for pilgrimage has deprived many pilgrims of legal protection, with numerous cases of arrests by Saudi authorities resulting in deportation and even a ten-year ban on entering Saudi Arabia. This study adopts a qualitative case study design with an empirical legal research approach. Data were collected through interviews and document analysis at PT Mirbath Tour and Travel Palu. The primary data source was an interview with the Director of PT Mirbath, while secondary sources included the Qur’an, Hadith, legislation, journals, articles, theses, dissertations, and reference books. Data analysis employed reduction, presentation, and conclusion drawing. The findings highlight three key points. First, PT Mirbath facilitated Hajj departures using multiple-entry visas with significant limitations, such as the absence of tents in Mina and Muzdalifah, restricted access to facilities, and alternative routes from Riyadh to bypass checkpoints. Second, the use of non-Hajj visas indicates that the implementation of Law of the Republic of Indonesia No. 8 of 2019 on the Administration of Hajj and Umrah has not been effectively enforced, with policy gaps and weak operational oversight remaining apparent. Third, although the contractual arrangements applied appear consistent with the principles of Islamic jurisprudence (fiqh muamalah), they conflict with the foundations of sharia economic law, as the use of non-Hajj visas involves elements of gharar (uncertainty), lack of transparency, and contractual objectives inconsistent with maqasid al-shariah.